Edgar Allan Poeâ€™s Narrative Use of Literary Doubling - Santiago, Miriam FernÃ¡ndez (Mediterranean Journal of Social Sciences, 2013)
The present article analyzes the incidence of the literary tradition of doubling in the short narratives of Edgar Allan Poe. Itpresents an analysis of doubling in Poeâ€™s short narratives from the different critical perspectives of previous research on literaryand non-literary doubling, and also from Poeâ€™s own views as a literary critic. It contends that Poeâ€™s compliant and subversiveuse of traditional literary doubling corresponds with his critical views on the compositional unity of effect as he developed themin â€œThe Philosophy of Composition.â€